Temperature-Dependent Ultrasonic Properties of Semiconducting M2CO2 (M= Ti, Zr, Hf) MXenes - Yadawa, P. K.; N. Chaurasiya; Rai, S.; Prajapati, A. K. (Journal of Scientific Research, 2022)
Here, we have studied the elastic, ultrasonic, mechanical, and thermal behavior of temperature-dependent hexagonal oxygen-functionalized M2CO2 (M= Ti, Zr, Hf) MXenes. The higher-order linear and nonlinear elastic constants, viz., second-order (SOECs), and third-order (TOECs) have been computed using the Lenard Jones interaction potential model. For mechanical characterization, bulk modulus (B), shear modulus (G), Young's modulus (Y), Pugh's ratio (B / G), Poisson's ratio, and anisotropic index are evaluated using SOECs. Born's stability and Pugh's criteria are used to examine the nature and strength of the MXenes in all the temperatures. For the investigation of anisotropic behavior and its thermophysical properties, temperature-dependent ultrasonic velocities and thermal relaxation time have been calculated along with different orientations from the unique axis of the crystal. The ultrasonic attenuation (UA) of a longitudinal and shear wave due to phonon-phonon (p-p) interaction and thermoelastic relaxation mechanism were investigated for these oxygen-functionalized MXenes. Thermal conductivity is a principal contributor to the behavior of UA due to p-p interactions. Our analysis suggests that semiconductor Ti2CO2 MXenes show superior mechanical properties to other oxygen-functionalized MXenes. Computed elastic, ultrasonic, and thermal properties are correlated to evaluate the microstructural behavior of the materials useful for industrial applications.